Penerapan Pemberian Teknik Tripod Position Dan Pursed Lip Breathing Terhadap Kenaikan Saturasi Oksigen Pada Pasien Sesak Di Ruangan IGD RSUD Prof. Dr. Aloe Saboe - Haslinda Damansyah; Susanti Monoarfa; Annisa A. Eyato (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Background: Most respiratory disorders are caused by problems or diseases of the respiratory system, including the lungs. Inability of the lungs to expand (elasticity), as well as structural (anatomical) and functional airway obstructions that prevent the creation of breathable airflow, are signs of impaired lung function. Restriction and blockage are two types of lung function problems.Purpose: To analyze the application of the tripod position and pursed lip breathing technique to the increase in oxygen saturation in congested patients in the emergency room at PROF Hospital. Dr. SABOE TONGUE.Methods: Case report, which is a narrative report. The case study in this paper examines the use of a tripod position and pursed lip breathing technique to increase oxygen saturation in shortness of breath patients. Patients with asthma, lung cancer, TB, and COPD constitute the study population. Four patients with asthma, lung cancer, tuberculosis, and COPD were sampled for the study.Results: After the nurse's intervention was carried out, which was related to airway management in the fourth patient, the overall evaluation results were obtained, then the intervention was continued in the patient's treatment room.Conclusion: Based on the description above, people with respiratory problems often experience decreased functional daily activities, decreased concentration, and mood swings. As a result, if the condition of shortness of breath is allowed to continue unnoticed it will reduce oxygen saturation which in turn can cause cyanosis in patients who experience recurrent infections.